Deferred recovery of health expenditures for pediatric life-threatening emergencies in a resource-limited setting: Alternative before achieving universal health coverage in Cameroon in Central Africa - Calixte Ida Penda; Charlotte Eposse Ekoube; Ritha Mbono Betoko; Cedric Nlend; Bertrand Eyoum Bilé; Francis Ateba Ndongo; Loic Boupda; Daniele Christiane Kedy Koum; Carole Eboumbou Moukoko; André Bita Fouda; Louis Richard Njock (PLoS ONE, 2025)
The lack of health cover in low-income countries is a real barrier to emergency care. The objective of our study was to evaluate the immediate management of pediatric emergencies by deferred recovery of the costs of care at Douala Laquintinie Hospital. A prospective cross-sectional study was conducted from 1st February to 30 June 2020 on patients admitted for life-threatening emergencies to the pediatric emergency department. Deferred recovery of healthcare costs was triggered by the issuance of a “green voucher, an internal reimbursement voucher issued by the doctor for expenses incurred upon patient admission in a life-threatening emergency and reimbursable within 72 hours after initial emergent management was received. Of the 786 patients admitted to the pediatric emergency department, 502 (63.8%) patients presented with a life-threatening emergency at a median age of 1 year [IQR: 0-5]. According to the indigence criteria, 40.4% of the patients were indigent and nearly 40% of the families’ patients declared having a monthly income < 50,000 franc of the French Colonies of Africa (FCFA) or 85 USD. The majority of patients with life-threatening 456 (90.8%) had benefited from the “green voucher” and 71.5% from care within 15 minutes of admission. The average household health expenditure during hospitalization was 143.9 ± 52.3 USD (53.5–393.9). A total of 76.1% of patients benefited from deferred care cost recovery, including 43.6% from moratorium payment facilities. The mortality rate was 9.8%. The deferred healthcare cost recovery system has proven effective in lowering avoidable child mortality in life-threatening emergencies, despite the heavy burden of healthcare costs for the underprivileged.